Next-gen approach to the combined micro/macro-scopic measurements of crystal growth in chalcogenide thin films: The case of Se90Te10 - Svoboda, Roman; Přikryl, Jan; Provotorov, Pavel; V. Kolobov, Alexander; Krbal, Miloš (Elsevier Science SA, 2022)
Crystal growth in 1 mu m Se90Te10 thin films deposited on a variety of substrates was studied by means of a novel combination of direct microscopic and calorimetric measurements. Differential scanning calorimetry (DSC) was used to explore the macroscopic manifestation of the crystal growth in as-deposited Se90Te10 thin films, revealing the native-like crystal growth behavior (very close to that of the bulk glass) in the films deposited on the polymeric foil. The optical microscopy determined the following sequence for the crystal growth rates u(r) in the thin films deposited on different substrates: u(r)(white glass) > u(r)(SiO2 glass) > > u(r)(Kapton). This finding is perfectly consistent with the calorimetric data, and can be explained by the combined influences of the Na+ ions migrating from the white glass substrate to the thin film/substrate interface, and by the compressive stresses arising from the large difference between the thermal expansion coefficients of Se90Te10 and the inorganic glasses. Conformation of the calorimetric and microscopic data was validated by the description of both datasets in terms of a single set of parametrized equations based on the combination of the temperature-resolved screw-dislocation growth model and the macroscopic nucleation-growth model. The novel approach to the crystal growth research in chalcogenide thin films was introduced, demonstrating its unprecedented accuracy, robustness and overall comprehension. All major aspects of this novel approach were discussed in detail, including the necessity to consider not only the substrate properties but also the associated process of structural relaxation that may significantly alter the crystal growth near glass transition. (C) 2022 Elsevier B.V. All rights reserved.
Nová generace přiblížení ke kombinovanému mikro/makro-skopickému měření krystalového růstu v chalkogenidových tenkých filmech: případ Se90Te10
Keywords: crystallization kinetics; structural relaxation; phase-change; selenium; nucleation; glasses; krystalizační kinetika; strukturní relaxace; fázová změna; selen; nukleace; skla